1996
DOI: 10.1074/jbc.271.35.21012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Three Potato Lipoxygenases with Distinct Enzymatic Activities and Different Organ-specific and Wound-regulated Expression Patterns

Abstract: Lipoxygenases are ubiquitous enzymes in eukaryotes. In plants, lipoxygenases are involved in the synthesis of the hormone jasmonic acid that regulates plant responses to wounding and, in addition, is an inducer of tuberization in potato. We have isolated potato lipoxygenase cDNA clones. From their deduced amino acid sequences, three distinct classes are defined (Lox1, Lox2, and Lox3). They are encoded in gene families that display organ-specific expression, lox1 being expressed mostly in tubers and roots, lox2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
202
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(218 citation statements)
references
References 40 publications
13
202
0
3
Order By: Relevance
“…The current picture of the LOX gene family in tomato thus resembles the situation in potato described by Royo et al (1996), with three classes identified to date on the basis of sequence similarity: the Loxl class includes TomLoxA and TomLoxB (Ferrie et al, 1994), the Lox2 class is represented by TomLoxC, and Lox3 is defined by TomLoxD. As shown for AtLOX2 (Bell et al, 1995) and suggested for rice RLL and for potato LOXZ and LOX3, the N-terminal extensions on both TomLOXC and TomLOXD might function as chloroplast transit peptides.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The current picture of the LOX gene family in tomato thus resembles the situation in potato described by Royo et al (1996), with three classes identified to date on the basis of sequence similarity: the Loxl class includes TomLoxA and TomLoxB (Ferrie et al, 1994), the Lox2 class is represented by TomLoxC, and Lox3 is defined by TomLoxD. As shown for AtLOX2 (Bell et al, 1995) and suggested for rice RLL and for potato LOXZ and LOX3, the N-terminal extensions on both TomLOXC and TomLOXD might function as chloroplast transit peptides.…”
Section: Discussionmentioning
confidence: 85%
“…More recently, additional Lox genes were cloned, and TomLoxC and TomLoxD were found to be highly similar to Lox2 and Lox3, respectively (Royo et al, 1996), two potato Lox genes that appear to be the homologs of the tomato genes described here. The overall identity of TomLOXC and TomLOXD with the previously cloned TomLOXA and TomLOXB (Ferrie et al, 1994) is relatively low.…”
Section: Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Following up on our P450 microarray, we analyzed CYP71B24, CYP706A1, CYP81D10, and CYP734A1, which were loci expressed at higher levels in the Col ecotype, as well as CYP83A1, CYP706A2, CYP707A3, and chalcone synthase-like (CHS-L), which were loci expressed at higher levels in the Ler ecotype. We also analyzed expression of the PR1-similar locus, the LOX2 locus that codes for a chloroplast 13-LOX providing substrates for HPL, and the LOX1 locus that codes for a 9-LOX not generating substrates for HPL (Royo et al, 1996;Blee, 2002). As shown in Figure 6, the expression patterns from RT-PCR analyses are generally in agreement with the P450 microarray results: Nearly all genes shown by microarray analysis to be expressed higher in one ecotype were also expressed higher in that ecotype by RT-PCR analysis.…”
Section: Transcript Profiling By Rt-pcr Analysismentioning
confidence: 99%